2017
DOI: 10.1111/jerd.12345
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide bleaching induces changes in the physical properties of dental restorative materials: Effects of study protocols

Abstract: The influence of study protocols on the effects of bleaching on the surface roughness, flexural properties, and color of dental restorative materials are material-dependent and should be considered when evaluating the effects of bleaching on dental restorative materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 24 publications
6
41
1
5
Order By: Relevance
“…During the bleaching procedure, not only the teeth surfaces but also the surface of pre‐existing restorative materials, comes into contact with the bleaching agents . These bleaching agents at high concentrations can promote a physical deterioration, mainly on surface roughness, of resin‐based composites (RBC) . It has already been demonstrated that surface roughness of RBC influence on optical properties and bacterial adherence .…”
Section: Introductionmentioning
confidence: 99%
“…During the bleaching procedure, not only the teeth surfaces but also the surface of pre‐existing restorative materials, comes into contact with the bleaching agents . These bleaching agents at high concentrations can promote a physical deterioration, mainly on surface roughness, of resin‐based composites (RBC) . It has already been demonstrated that surface roughness of RBC influence on optical properties and bacterial adherence .…”
Section: Introductionmentioning
confidence: 99%
“…Auch die Frage, ob es infolge des Bleichens zu einer Erhöhung der Oberflächenrauheit von Kompositfüllungen kommt, wird je nach Studiendesign unterschiedlich beantwortet. So beschrieben mehrere Autoren eine Zunahme der Rauigkeit [49,50] sowohl für stopfbare als auch für fließfähige Komposite nach der Polymerisation und Applikation verschiedener Bleichmaterialien [49].…”
Section: Oberflächenrauheitunclassified
“…Yu ve ark., hidrojen peroksitin yedi farklı kompozit materyali üzerindeki beyazlatıcı etkisini araştırmışlardır. 30 Araştırmacılar, çalışmalarının sonucunda, hidrojen peroksit uygulamasının çalışmada kullanılan bütün kompozitlerin yüzey pürüzlülük değerini artırdığını ve test edilen tüm örnekler için (seramik materyali hariç) belirgin bir renk değişimi oluşturduğunu ifade etmişlerdir. Beyazlatma işleminin restoratif materyallerin fiziksel özellikleri üzerinde farklı etkiler oluşturduğunu ve bu etkilerin kullanılan materyale bağlı olduğunu bildirmişlerdir.…”
Section: Gereç Ve Yöntemlerunclassified
“…Beyazlatma işleminin restoratif materyallerin fiziksel özellikleri üzerinde farklı etkiler oluşturduğunu ve bu etkilerin kullanılan materyale bağlı olduğunu bildirmişlerdir. 30 Alharbi ve ark., ofis tipi beyazlatma ajanının, renklendirilmiş rezin kompozit ve CAD/CAM blokları üzerine etkinliğini değerlendirmişlerdir. Araştırmacılar, çalışmamız ile benzer şekilde, hidrojen peroksit uygulamasının dental restoratif materyal üzerindeki renklenmeleri gidermede etkin bir yol olduğunu bildirmişlerdir.…”
Section: Gereç Ve Yöntemlerunclassified